공공임대주택 공급체계의 이원화 방안 연구 - 조흥연(Cho, heungyeon); 이춘원(Lee, chunwon) (대한부동산학회지, 2021)
1970년대 이후 급격한 도시화에 따른 열악한 주거환경을 개선하기 위하여 정부는 LH공사 중심의 물량 위주 공급을 통하여 OECD 10위권의 공공임대주택 재고율을 확보하였다. 하지만 2000년대 인구 감소와 저성장시대에 접어들면서 기존의 공급방식이 더 이상 유효하지 않게 되었다. 2010년대 이후 공공지원 민간임대주택, 역세권 청년주택, 사회주택 등 다양한 방식의 공공임대주택을 공급하여 큰 호응을 얻었지만 공급은 큰 폭으로 증가하지 못하였다. 한편, 임대주택 구조론 관점에서 행복주택과 주거복지로드맵 등의 정책을 고려할 때, Kemeny의 이론에 따르면 이원적 임대모델에서 단일적 임대모델로, Harloe의 이론에 의하면 잔여모델에서 대중모델로 전환하는 과도기적인 과정으로 판단된다. 이 연구는 기존 LH공사의 공공형 공공임대주택 공급방식에 더하여 새로운 공급방식을 제안하고자 한다. 즉, HUG가 직접 공모 또는 지방자치단체 협업방식으로 그간 체계 없이 공급한 행복주택과 사회주택 등을 공공지원방식으로 통합 관리하여 민간 사업자의 시장논리와 지역특성을 반영한 공급을 지원하는 시장형 공급방식을 제안한다. 이를 통하여 LH공사는 저소득계층을, HUG 등은 청년, 신혼부부 등 소득분위 4~6분위 계층을 대상으로 공공임대주택을 공급하는 이원화된 공급체계를 구성한다. Since the 1970s, in order to improve the poor residential environment due to rapid urbanization, the government has secured the inventory rate of public rental housing in the top 10 in the OECD through supply centered on LH Corporation. However, as the population declined and entered the era of low growth in the 2000s, the past supply method was no longer valid. Since the 2010s, it has been well received by supplying various types of public rental housing such as public-supported private rental housing, station-based youth housing, and social housing, but the supply has not increased significantly. On the other hand, considering policies such as happy housing and residential welfare road-map from the perspective of rental housing structure theory, according to Kemeny's theory, it is in the process of switching from a dualist rental model to a unitary rental model, and according to Harloe's theory, it is a process of switching from a residual model to a mass model. This study aims to propose a new supply method in addition to the existing LH Corporation's public rental housing supply method. In other words, HUG proposes a market-type supply method that supports the supply according to the market logic of private businesses by integrating and managing happy housing and social housing that have been supplied without a system through direct public offering or cooperation with local governments. Through this, LH Corporation will supply public rental housing to low-income families, and HUG and others will supply public rental housing to the 4th to 6th quintiles of income, such as young people and newlyweds, to form a dualization supply system. KCI Citation Count: 0